Effects of Apelin on Cardiovascular Aging - Zhou, Ying; Wang, Yong; Qiao, Shubin; Yin, Liang (Frontiers in Physiology, 2017)
Apelin is the endogenous ligand for the previously orphaned G protein-coupled receptor, APJ. This novel peptidic signalling pathway is widely represented in the heart and vasculature, and is emerging as an important regulator of cardiovascular homeostasis. Apelin–APJ signalling has has long been linked to diseases prominent in the elderly such as hypertension, atherosclerosis, coronary atherosclerotic heart diseases, heart failure, atrial fibrillation and calcific aortic valve disease (CAVD). In this review, we focus on the Apelin–APJ signalling pathways involved in age-associated vascular changes and in the development of age-related cardiovascular diseases (CVDs). In addition, we briefly describe Apelin–APJ’s potential in improving the health of the elderly population.